An injectable, click-crosslinked, cytomodulin-modified hyaluronic acid hydrogel for cartilage tissue engineering - Park, Seung Hun; Seo, Ji Young; Park, Joon Yeong; Ji, Yun Bae; Kim, Kyungsook; Choi, Hak Soo; Choi, Sangdun; Kim, Jae Ho; Min, Byoung Hyun; Kim, Moon Suk (NPG Asia Materials, 2019)
This is the first report, to our knowledge, of the preparation of an injectable in situ–forming click-crosslinked hyaluronic acid (Cx-HA) hydrogel (Cx-HA-CM) containing chemical immobilized cytomodulin-2 (CM), a chondrogenic differentiation factor, and on the utility of human periodontal ligament stem cells (hPLSCs) as a cell source for cartilage tissue engineering. hPLSCs served here as a stem cell source tolerant to ex vivo manipulation. CM induced in vitro chondrogenic differentiation of hPLSCs comparable to induction with traditional TGF-β. Cx-HA was prepared via a click-reaction between tetrazine-modified HA and transcyclooctene-modified HA. Cx-HA displayed significantly more features of a stiff hydrogel than HA. Cx-HA had a three-dimensional porous interconnected structure, absorbed a large volume of biological medium, and showed excellent biocompatibility. In contrast to HA, the Cx-HA hydrogel persisted in vitro and in vivo for an extended period, as evidenced by in vivo near-infrared fluorescence imaging. CM covalently linked to Cx-HA (Cx-HA-CM) remained inside Cx-HA for a prolonged period compared with CM physically loaded onto Cx-HA [Cx-HA (+CM)]. Cx-HA-CM also caused better chondrogenic differentiation of hPLSCs, as evidenced by Alcian blue and Safranin O staining, and greater increases in the expression of type II collagen, glycosaminoglycan content and SOX9, aggrecan, and type 2α1 collagen mRNA levels. Thus, compared to Cx-HA (+CM), the hPLSC-loaded Cx-HA-CM hydrogel induced greater chondrogenic differentiation of hPLSCs via CM that was retained in the hydrogel for a much longer period of time.
Keywords: Cartilage tissue engineering; Chondrogenic differentiation; Glycosaminoglycans; Human periodontal ligament; Hyaluronic acid hydrogels; Interconnected structures; Near-infrared fluorescence imaging; Type II collagens